(untitled) (Jurnal Teknologi (Sciences & Engineering), 2019)
This study investigates the bending and bonding performances of glued laminated timber beams manufactured using a combination of Malaysian lower and higher- grade timber species. Two types of beams were prepared which were mono-species and mixed-species glulam. Mono-species glulam with uniform layup were fabricated using Merpauh, Jelutong and Sesendok. Mixed-species glulam with balanced layup were fabricated whereby Merpauh was positioned equally at the outer layers and either Jelutong or Sesendok were positioned at the inner layers. Three replicates of ten-layered glulam beams measuring 100 mm in width, 300 mm in depth and 6200 mm in length were manufactured according to MS758 for each mono and mixed-species glulam. Bending, delamination and block shear tests were done on all the glulam beams. The results show that glulam manufactured from the combination of Sesendok and Merpauh obtained the highest bending properties and structural efficiency. In addition, the bonding performance at the interface between Sesendok-Merpauh lamellas proved to be excellent.